Pengembangan Media Pembelajaran Berbasis Teknologi Augmented Reality (AR) dengan Algoritma Vuforia SDK pada Mata Pelajaran IPA Kelas VIII di Madrasah Al-Aqsha (MTS) - Aryanti, Putri Gea; Rasiban; Sarimole, Frencis Matheos; Tundo (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to develop learning media in the form of an Android-based Augmented Reality application on human respiratory system material which can provide information about the introduction of respiratory system organs and their processes, and markerless images of the shapes of the organs which have been input into the Vuforia SDK library. This research develops an Augmented Reality application as an introduction to the organs of the respiratory system using several tools such as: MDLC, Unity, ARToolkit to better understand students about the respiratory system. The application of Augmented Reality in this research uses the Marker Based methods. The Augmented Reality application for recognizing the respiratory system in humans was tested using BlackBox with results of passing the system functional test 100% and usability testing results using a questionnaire. The learnability aspect was 4.47, efficiency 4.43, memorability 4.2, errors 4.5, and satisfaction 4.52, this application was tested in the